Alpha-Fetoprotein and Hepatocellular Carcinoma Immunity - Xiaoping Wang; Qiaoxia Wang (Canadian Journal of Gastroenterology and Hepatology)
Hepatocarcinoma is one of the most prevalent gastroenterological cancers in the world with less effective therapy. As an oncofetal antigen and diagnostic marker for liver cancer, alpha-fetoprotein (AFP) possesses a variety of biological functions. Except for its diagnosis in liver cancer, AFP has become a target for liver cancer immunotherapy. Although the immunogenicity of AFP is weak and it could induce the immune escapes through inhibiting the function of dendritic cells, natural killer cells, and T lymphocytes, AFP has attracted more attention in liver cancer immunotherapy. By in vitro modification, the immunogenicity and immune response of AFP could be enhanced. AFP-modified immune cell vaccine or peptide vaccine has displayed the specific antitumor immunity against AFP-positive tumor cells and laid a better foundation for the immunotherapy of liver cancer.